Synthesis of zinc-layered hydroxide and zinc-aluminium-layered double hydroxide as host of ultraviolet ray absorbing molecules for sunscreen application - Megat Nabil Mohsin, Sumaiyah (2014)
New sunscreen formulation was formulated with the intercalation of organic ultraviolet (UV)-ray absorbing molecules into two layered materials; namely zinc layered hydroxide (ZLH) and Zn/Al layered double hydroxide (LDH). Intercalation in inorganic matrix was attempted with the intention of maintaining UV absorption properties of the otherwise photodegradable organic molecules. Furthermore, ZLH and LDH as host carriers provide a barrier between skin and chemical compounds and consequently prevent the phototoxic and photoallergic reactions. ZLH intercalated with cinnamate (CA) was successfully synthesized using direct reaction of zinc oxide (ZnO) and cinnamic acid. The intercalated compound, ZCA, has a basal spacing of 23.9 Å, with the estimated percentage loading of CA around 40.4 w/w %. The intercalation of benzophenone 9 (B9) into Zn/Al LDH was carried out by two different routes; co-precipitation and ion exchange method. Powder x-ray diffraction (PXRD) patterns of the co-precipitated product (ZB9C) and ion exchanged product (ZB9I) showed basal spacing of 15.9 Å and 16.6 Å, respectively. The percentage loading of B9 anions is 46.6 w/w % for ZB9C and 43.9 w/w % for ZB9I. The intercalation of CA, benzophenone 4 (B4) and eusolex® 232 (EUS) into Zn/Al LDH was also successfully performed via co-precipitation method with the expansion of basal spacing from 8.8 Å in Zn/Al LDH to 17.9 Å, 21.3 Å and 21.0 Å, respectively. Percentages loading of CA, B4 and EUS anions in Zn/Al LDH host are 35.8 w/w %, 41.9 w/w % and 41.7 w/w %, respectively. Co-precipitation of equimolar concentration of B4 and EUS with Zn/Al LDH host showed an intercalation selectivity that is preferential to EUS. It was also shown that the selectivity ratio of intercalated anions was altered by varying molar ratio of guests during the synthesis. Dual-guest nanocomposite synthesized with B4:EUS molar ratio 3:1 (ZEB (3:1)) showed an intercalation percentage of 20.5 w/w % for B4 and 17.9 w/w % for EUS. The selectivity ratio of B4:EUS could be rephrased as 53:47. ZEB (3:1) nanocomposite was monitored using PXRD and showed a basal spacing of 21.8 Å, which is slightly larger than single intercalation product of B4 and EUS in Zn/Al LDH. The solid-state absorbance spectra of UV absorbent-intercalated compounds showed broadened UV absorptivity range compared to pure UV absorbent due to the spatial confinement and host-guest interactions. Retention study of sunscreen molecules in ZLH and LDH was conducted with various release media; namely deionized water, pH 5.5 phosphate buffer (skin pH simulation) and 0.5 mol/L NaCl solution (artificial sea water), to observe nanocomposites performance in close to actual application. Anion release patterns in release media showed a slowed and restricted deintercalation from inorganic host. The cytotoxicity study of intercalation compounds on human dermal fibroblast (HDF) cells was investigated using Methylthiazol Tetrazolium (MTT) assay. In general, 24 h exposure with nanocomposites did not produce any significant cytotoxicity up to maximum concentration of 25 μg/mL. In brief, the UV absorbent/layered material system show great promise as a safe and efficient sunscreen formulation with prolonged UV protection effect.